A short review of the impact of wooden panels on room acoustics - Tomasz Rogozinski; Marlena Wojnowska (Global Forest Journal., 2026)
The article provides an overview of information on the impact of wood panels and wood-based composites on room acoustics. It focuses on key parameters such as reverberation time (RT), sound absorption, and speech and music clarity (Clarity, STI). Wood-based panels and composites show strong potential as sustainable acoustic solutions, reducing reverberation time and improving clarity, while requiring careful optimization of porosity, thickness, and perforation to balance performance across frequencies